Gambaran Dokumentasi Asuhan Keperawatan Keluarga di Puskesmas - Milda Nurul Fitriani; Iwan Shalahuddin; Neti Juniarti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2020)
Introduction: Nursing documentation based on nursing care standards must provide quality nursing services and care by nurses. The incompleteness of documentation will cause the enforcement of inappropriate diagnosis that make the care given less than optimal. Objective: The purpose of this research was to determine the family nursing documentation in the Health Center. The research carried out in Haurpanggung Health Center by conducting documentation studies on 250 nursing care documents. Method: This research used quantitative descriptive by collecting all documentation of family nursing care made by nurses and professional nurses. Using univariate analysis conducted with descriptive analysis to see the percentage of each variable studied. Result: Based on the results of research on nursing care documentation in Haurpanggung Health Center Garut in 250 documents that most of the completeness of family nursing care has a fairly good completeness. so that we can see the most types of diagnostic formulations and the most types of interventions that can be used as a database for electronic virginity care and can make it easier to make nursing care. Conclusion: The results of this study are expected to be used in Health Center as a basic data for health workers to design efforts to improve documentation especially in filling / recording nursing care properly.